Recursixeness In Written Feedback - Kumar, Margaret; Kumar, Vijay; Feryok, Anne (2009)

(untitled)
Studies on written feedback have reported on writers' perceptions of feedback. However, these studies have relied on observations, questionnaires, checklists, classroom observations, retrospective interviews, and textual analysis of written feedback. What seems to be lacking in the literature is an in-depth understanding of the thought processes of students when they attend to written feedback. In this paper, we report on a case study that investigates cognitive processes and reactions when a postgraduate student of Confucian Cultural Heritage attends to written feedback. Concurrent verbal protocols used in conjunction with written drafts and questionnaires form the data source for this study. Our analysis shows that attending to feedback is an ongoing recursive process. Secondly, this case study suggests that recursiveness prompts discovery in writing. Finally, this study indicates that although cultural attributes are often mentioned in relation to Confucian Heritage Culture learners, in this case these attributes did not appear to play a strong role.